Compactação do solo nas camadas agricultáveis nos sistemas de plantio direto e cultivo mínimo - Melo, Dirceu de (2006)
The handling systems can affect physical qualities of agricultural soils as density and porosity, as well as the organic matter reserves distributed on agricultural layer s profile. This trial aimed at evaluating the effect of no-tillage and minimum tillage systems: no-tillage system during four consecutive years (NT4); minimum tillage after four consecutive years with direct no-tillage system (MT4); no-tillage system during eight consecutive years (NT8) and; minimum tillage after eight consecutive years with no-tillage system (MT8). Cultures as soybean and maize were carried out in this field, the first one on summertime and the second in the winter with the same motomechanized sets for sowing, spraying and harvesting activities. The yield of soybean culture, soil s density, particle density, organic matter, total porosity, porosity of adding (microporosity) and structural porosity (macroporosity) were evaluated, regarding depths from 0 to 0.05; 0.05 to 0.10; 0.10 to 0.15 and 0.15 to 0.20 m, which were collected at three different periods: one day after the culture s implantation; 60 days after the sowing and on the harvest day. This trial was carried out in Distroferric Red Latosoil, in Medianeira (PR). The results showed that soil s density decreased with the MT4 and MT8 minimum tillage systems; and the total porosity and structural porosity increased proportionally when density decreased. The average results from organic matter were statistically similar for all the tillage systems, even though they have shown a significantly difference among the studied layers, with the greatest value. The band of the worked area has four and eight years with no-tillage were evaluated in relation to the water text in the ground of 10 to 24% and 15 to 24% respectively. The soybean yield was 12 % greater for the NT4 and NT8 no-tillage systems.